Analisis Kemampuan Berpikir Kritis Matematis Berbasis Realistik - Indri Anugraheni; E. Kus Eddy Sartono (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The purpose of this study is to describe students' critical thinking skills in realistic-based. This research is a qualitative descriptive study. The subjects of this study were students of Elementary School Teacher Education, FKIP, Satya Wacana Christian University in mathematics courses. The data collection technique in this study was a test of students' critical thinking skills. The results of the critical thinking test were analyzed by describing the students' critical thinking skills in the fraction operation. Based on the results of the study, it is known that: 1) students of elementary school teacher candidates need to improve their ability to generalize in teaching addition, subtraction and division arithmetic operations with the same denominator; 2) students need assistance and improvement in their ability to analyze the addition and multiplication count operations with the same denominator; 3)students need assistance and increase their ability to generalize to the addition and subtraction of fractions with different denominators, 4) Students need assistance in improving their ability to analyze multiplication and division counting operations on different denominators.